PERANAN KPPU DALAM PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT AKIBAT PERSEKONGKOLAN (STUDI KASUS PUTUSAN NO. 14/KPPU-L/2019) - Lesson Sihotang (LPPM Universitas HKBP Nommensen, 2021)
Within 1 (one) year, the increase in cases of tender conspiracy has increased. This shows that many business actors from these actions taken to practice are still in business, which results in unfair competition in doing business. The purpose of this research is to find out how KPPU proves the existence of a tender conspiracy related to Decision No. 14/KPPU-L/2019 and to find out the application of the law according to Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition by the judge in decision no. 14/KPPU-L/2019. Conducting this research using library research methods and data analysis used in a qualitative descriptive way is an approach to gain depth, develop theory and social complexity. The writer concludes that in carrying out the proof, KPPU uses the rule of reason and the per se illegal approach. The application of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition by judges related to decision no. 2019 uses an animation stream and a progressive stream which produce an explanation of the relevant laws and regulations, about vertical conspiracy, and about fulfilling the elements of article 22 of Law No. 5 of 1999.